Determination of trace bisphenols in functional beverages through the magnetic solid-phase extraction with MOF-COF composite. (30th May 2021) - Jiang, Hai-Long; Fu, Quan-Bin; Wang, Ming-Lin; Lin, Jin-Ming; Zhao, Ru-Song
Highlights: A novel MOF-COF composite (Fe3 O4 @TAPB-COF@ZIF-8) was synthesized with a facile strategy. Fe3 O4 @TAPB-COF@ZIF-8 is an ideal material for magnetic solid-phase extraction of bisphenols. Green and effective method to quantify bisphenols in food samples was established. The method showed high recovery, wide linear range and low detection limit. Abstract: In this study, a novel porous composite (Fe3 O4 @TAPB-COF@ZIF-8) consisting of metal–organic and covalent organic frameworks was developed and applied to the magnetic solid-phase extraction (MSPE) of bisphenols. The extraction parameters such as the extraction time, solution pH, amounts of adsorbent, and ionic strength were investigated to obtain the best extraction conditions. By optimizing the MSPE, a convenient and sensitive analytical method was established in combination with high-performance liquid chromatography. The method achieved low detection limits (0.04–0.05 ng mL −1 ), wide linear range (0.25–1000 ng mL −1 ), good repeatability (1.20–4.30%), good reproducibility (1.34–4.03%), and satisfactory recoveries of four functional beverages (66.2–116.6%).